Changes in interlanguage complexity during study abroad: A meta-analysis. (February 2019) - Xu, Yiran
Abstract: Despite the growing interest in interlanguage complexity development in study abroad (SA) research, no clear-cut conclusions can be made as to whether and to what extent learners' interlanguage complexity increases following a sojourn abroad. The current study meta-analyzed the overall effects of study abroad on measured oral and written complexity, as well as the moderator effects (i.e., learner demographics, SA contextual features, and outcome measures) on the variability of interlanguage complexity effect sizes (Cohen's d ). A comprehensive search was conducted to obtain studies that have quantitatively documented lexical and syntactic complexity changes during SA through a pre-and-post SA design. A total of 30 independent samples from 28 primary studies involving 602 participants were retrieved and coded for gains and for moderator variables. Results show an overall small effect of study abroad on language complexity development ( d = 0.37). In addition, moderator analyses suggest that larger effects are associated with (a) learners at an intermediate proficiency level, (b) learners enrolled in a language study program while SA, (c) programs that implemented a language pledge, or (d) programs with Mandarin Chinese as the target language. More fine-grained and systematic reporting practices are proposed for future research.